Kegiatan Pelatihan Praktik Ibadah Sholat untuk Meningkatkan Pengetahuan dan Pemahaman pada Anak Usia Dini di Desa Jaddih Selatan, Kecamatan Socah, Kabupaten Bangkalan - Irfan Nofa Sagita; Farhan Farhan; Sholehuddin Sulaiman (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community engagement program aims to enhance the knowledge and understanding of early childhood regarding prayer practices through a series of interactive and practice-based training sessions. Targeting children aged 5–7 years in Jaddih Selatan Village, Bangkalan, the program utilized a participatory approach involving local religious leaders, parents, and university students as facilitators. The training was conducted at the village mosque, employing visual aids, demonstrations, and repeated simulations to foster both cognitive and psychomotor aspects of prayer. The results indicate a significant improvement in children's ability to perform prayer movements and recitations correctly, as well as increased enthusiasm and participation in religious activities. Moreover, the program strengthened the mosque's role as a child-friendly religious learning center and encouraged the emergence of leadership potential among the participants. This initiative is expected to serve as a sustainable model for character education and spiritual development in rural communities, and can be replicated in similar settings to empower early childhood religious education.